2017
DOI: 10.3390/nu9070713
|View full text |Cite
|
Sign up to set email alerts
|

Feeding a Mixture of Choline Forms during Lactation Improves Offspring Growth and Maternal Lymphocyte Response to Ex Vivo Immune Challenges

Abstract: Study objectives were to examine the impact of feeding a mixture of choline forms, or a diet high in glycerophosphocholine (GPC) on maternal immune function and offspring growth during lactation. Lactating Sprague-Dawley rat dams (n = 6/diet) were randomized to one of three diets, providing 1 g/kg total choline: Control (100% free choline (FC)), Mixed Choline (MC; 50% phosphatidylcholine (PC), 25% FC, 25% GPC), or High GPC (HGPC; 75% GPC, 12.5% PC, 12.5% FC). At 3 weeks, cell phenotypes and cytokine production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Emerging evidence has highlighted a role for maternal choline supplementation in promoting placental health (22)(23)(24)(25) and in reducing placental production of corticotropinreleasing hormone via epigenetic mechanisms (3). In addition to choline's role during pregnancy, emerging research demonstrates that higher choline intakes during lactation improve breast milk choline content (26,27) and that the form of choline in the maternal diet influences the development of the offspring's immune system (28,29).…”
Section: Recent Researchmentioning
confidence: 99%
“…Emerging evidence has highlighted a role for maternal choline supplementation in promoting placental health (22)(23)(24)(25) and in reducing placental production of corticotropinreleasing hormone via epigenetic mechanisms (3). In addition to choline's role during pregnancy, emerging research demonstrates that higher choline intakes during lactation improve breast milk choline content (26,27) and that the form of choline in the maternal diet influences the development of the offspring's immune system (28,29).…”
Section: Recent Researchmentioning
confidence: 99%
“…FSC/SSC gating was used to identify lymphocytes, and the CD3 and CD8/CD4/CD45RA/CD161 bivariate analysis identified the CD8+ T, CD4+ T, CD3-CD45RA+ B, CD3-CD161+ NK (bright), CD3-CD161+ NK (dim). CD3-CD45RA+ is often used to identify B cells in rats, and CD3-CD161+ is used to identify natural killer cells (31)(32)(33).…”
Section: Detection Of Lymphocyte Subtypes In Ratsmentioning
confidence: 99%
“…We have also shown that feeding 100% soy-PC in a maternal diet in Sprague-Dawley rats increased IL-2 production in mesenteric lymph nodes (MLNs) but not splenocytes [ 21 ]. Further, our laboratory showed that feeding a mixture of choline forms in the maternal diet composed of 50% soy-PC had no effect on IL-2 production but did lead to an overall more efficient Th1 immune response [ 22 ]. Altogether, this suggests that there may be a differential effect on immune function between egg- and soy-derived PC.…”
Section: Introductionmentioning
confidence: 99%